2013
DOI: 10.1589/jpts.25.765
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Abdominal Muscles Balance and Body Balance

Abstract: This study aimed to identify what impact the thickness differences between the leftside and rightside transversus abdominis (TrA), internal obliquus (IO) and external obliquus (EO) have on balance ability in the abdominal drawing-in maneuver (ADIM) and resting postures. [Subjects and Methods] In this study, 41 young adults were asked to adopt a resting posture and to perform ADIM. The thicknesses of the abdominal muscles (TrA, IO, EO) were measured using ultrasound imaging, Then balance ability was measured, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…The TrA allows functional movements by stabilizing every segment of the lumbopelvic region when supporting the body's weight [14]. Stable and strong core muscles contribute to more efficient use of the upper and lower limbs and are important for the successful performance of day-to-day activities during old age [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TrA allows functional movements by stabilizing every segment of the lumbopelvic region when supporting the body's weight [14]. Stable and strong core muscles contribute to more efficient use of the upper and lower limbs and are important for the successful performance of day-to-day activities during old age [51].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the relationship between back and abdominal muscle functions and quality of life [12], spinal mobility [13], and postural balance [14], but none of the studies had focused on the correlation of back and abdominal muscle function and functional performance. These muscle functions may influence the functional performances in older persons, especially for those who have had LBP, yet the association between muscle functions and functional performances has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…El fortalecimiento de la fuerza resistencia de la musculatura abdominal, permite la estabilidad a la altura de las vértebras lumbares, permitiendo tener calidad en los movimientos funcionales y proporcionando estabilidad a cada segmento de la región lumbo -pélvica, encargada de soportar el peso del cuerpo. (Seo, et al 2013) Fisiología de la fuerza resistencia…”
Section: Fuerza Resistenciaunclassified
“…This can lead to improved cardiopulmonary function and reduced respiratory distress symptoms [3]. In the study by Seo et al [4], joint mobilization applied around the spine was reported to enhance symmetry in the muscles of the trunk. Additionally, the research by Jang and Bang, Jang [5].…”
Section: Introductionmentioning
confidence: 99%